Thermodynamic Effect Of Tetra-N-Butylammonium Hydroxide On CO2 Hydrate Promotion - Param Kumar, Vanisha Kumar (Universiti Teknologi PETRONAS, 2016)
Global warming is the gradual increase in Earth’s average surface temperature primarily due to the emission of greenhouse gases such as CO2. The removal of CO2 from atmosphere is very crucial. There are several commercial separation methods used to capture CO2 such as membrane separation, cryogenic separation, adsorption and absorption but all these methods have significant drawbacks such as low capacity and high energy consumption that make it an unsuitable technology. Recent studies and research are being done extensively to replace the commercial CO2 capture methods. Gas hydrate crystallization has been proposed to be a promising new approach to separate CO2 from flue gas as it has many advantages. Nevertheless, gas hydrate also has its drawback for instance the formation of gas hydrate in nature requires high pressure and low temperature condition. The most common way of overcoming this drawback is by adding chemical additives known as hydrate promoter in the hydrate formation process.